Solving standard dynamic motion problems using Fortran / Nik Haslina Mohd Hatta - Mohd Hatta, Nik Haslina (2002)
This project, "Solving Standard Dynamic Motion Problems Using Fortran" is essentially a demonstration of how computer programmes can improve the solutions to engineering problems in terms of efficiency and accuracy; narrowed down to how common kinematics and kinetics problems can be more effectively solved by means of Fortran programming. The phrase "common kinematics and kinetics problems" refers to problems which are familiar to undergraduate scholars in the sense these problems recurrently appear in any dynamics text/reference book. This project sufficiently covers the topics of Kinematics and Kinetics of Particles, and Kinematics and Kinetics and of Rigid Bodies (both in 2-D and 3-D). The bulk of this dissertation comes from the working and methodology in obtaining the solutions of example problems via both the manual and computerised means, all of which are located in Chapter V: Presentation of Project. This dissertation is accompanied by a compact disc containing all of the Fortran programmes written to solve different dynamic motion problems.